Dead witch walking - Harrison, Kim. (New York : HarperTorch, 2004)
Rachel Morgan, a witch and bounty hunter, works in "the Hollows" of Cincinnati where vampires rule the darkness.
Keywords: Witches -- Fiction; Vampires -- Fiction; Bounty hunters -- Fiction; Cincinnati (Ohio) -- Fiction; Occult fiction